2017
DOI: 10.1071/cp17183
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors affect seed germination and seedling emergence of invasive Centaurea balsamita

Abstract: Centaurea balsamita is a problematic and invasive weed of agricultural fields in western Iran. This study was conducted to determine the effect of different environmental factors on germination and seedling emergence of this weed species. Results revealed that seed germination occurred over a wide range of temperatures (from 5°C to 35°C) with the highest germination at 25°C. Seed germination of C. balsamita was similar between light and dark conditions. Germination decreased with increased in water stress level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Germination of both seed types of T. arvensis in the presence or absence of light was the same and was not affected by light. Similar to our results, the insensibility of weed seeds to light for germination (nonphotoblastic) has been reported for many other species, such as Centaurea balsamita Lam (Nosratti et al 2017c), Myagrum perfoliatum (Honarmand et al 2016), Sophora alopecuroides (Nosratti et al 2017a), Solanum ptycanthum Dun (Zhou et al 2005) and Ipomoea purpurea Roth (Singh et al 2012).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Germination of both seed types of T. arvensis in the presence or absence of light was the same and was not affected by light. Similar to our results, the insensibility of weed seeds to light for germination (nonphotoblastic) has been reported for many other species, such as Centaurea balsamita Lam (Nosratti et al 2017c), Myagrum perfoliatum (Honarmand et al 2016), Sophora alopecuroides (Nosratti et al 2017a), Solanum ptycanthum Dun (Zhou et al 2005) and Ipomoea purpurea Roth (Singh et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, the insensibility of weed seeds to light for germination (nonphotoblastic) has been reported for many other species, such as Centaurea balsamita Lam (Nosratti et al . ), Myagrum perfoliatum (Honarmand et al . ), Sophora alopecuroides (Nosratti et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the yield losses under saline conditions observed in our study, it has to be considered that the medium level tested (S1: 4.0 dS/m) which provoked a small yield loss is usually prohibitive for plant growth of many conventional leafy crops and results in severe losses of yield [56,57]. So far, there are reports regarding the response of other Centaurea genus members to salinity stress [58][59][60][61], including some halophytic species of the genus [62,63]. However, to the best of our knowledge this is the first report regarding the impact of salinity on plant growth of C. raphanina subsp.…”
Section: Plant Growthmentioning
confidence: 68%
“…plants had a long vegetation period. Nosratti et al (2017b) reported that while the best germination percentage was observed at 25 °C in C. balsamita taxon, the light and dark conditions had similar effects on seed germination of C. balsamita. Noting that the responses of different Centaurea species to the light period were not comparable, Köse and Yücel (2015) monitored varying photoperiod conditions and germination percentages at 25 °C in four different Centaurea taxa.…”
Section: Determination Of Seed Germination Performances At Different ...mentioning
confidence: 93%